2010
DOI: 10.1051/0004-6361/201014663
|View full text |Cite
|
Sign up to set email alerts
|

Herschel-ATLAS: The angular correlation function of submillimetre galaxies at high and low redshift

Abstract: We present measurements of the angular correlation function of galaxies selected from the first field of the H-ATLAS survey. Careful removal of the background from galactic cirrus is essential, and currently dominates the uncertainty in our measurements. For our 250 μm-selected sample we detect no significant clustering, consistent with the expectation that the 250 μm-selected sources are mostly normal galaxies at z < ∼ 1. For our 350 μm and 500 μm-selected samples we detect relatively strong clustering with c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 25 publications
7
46
2
Order By: Relevance
“…38) shows that roughly (14±8)% of DSFGs with S 250 > 30 mJy appear as satellites in more massive halos than ∼ 10 12 M . We note that slightly different results related to galaxy clustering at Spire wavelengths is reported in Maddox et al (2010). At low-redshifts with z < 0.5, the clustering of DSFGs are similar to blue, star-forming galaxies with a correlation length ∼ 4.6 ± 0.5 Mpc Guo et al, 2011) and are less-clustered than the dark matter distribution with a linear bias factor less than one (b = 0.7 ± 0.1).…”
Section: Clustering Of Dsfgscontrasting
confidence: 50%
“…38) shows that roughly (14±8)% of DSFGs with S 250 > 30 mJy appear as satellites in more massive halos than ∼ 10 12 M . We note that slightly different results related to galaxy clustering at Spire wavelengths is reported in Maddox et al (2010). At low-redshifts with z < 0.5, the clustering of DSFGs are similar to blue, star-forming galaxies with a correlation length ∼ 4.6 ± 0.5 Mpc Guo et al, 2011) and are less-clustered than the dark matter distribution with a linear bias factor less than one (b = 0.7 ± 0.1).…”
Section: Clustering Of Dsfgscontrasting
confidence: 50%
“…For the 250 μm channel on Herschel, for example, this means that no matter how deeply you observe a field, without some sort of spatial deconvolution at best only ∼15% of the flux density will be resolved into individually detected galaxies (Oliver et al 2010b). Adding to that the fact that the redshift distribution of DSFGs is relatively broad (e.g., Casey et al 2012;Chapman et al 2005;Béthermin et al 2012c), clustering measurements of resolved sources have consequently had limited success (e.g., Blain et al 2004;Scott et al 2006;Weiß et al 2009) and somewhat contradictory results (e.g., Cooray et al 2010;Maddox et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Gilli et al (2007) showed a correlation function of Spitzer MIPS 24-μm-selected galaxies at z ∼ 1, whose power-law slope is ∼1.5. Maddox et al (2010) analyzed the clustering of submillimeter galaxies detected by Herschel in the H-ATLAS survey. They have found a very steep slope of γ ∼ 2.0.…”
Section: Extraction Of the Spatial Properties Of The Correlation Funcmentioning
confidence: 99%
“…More recently, the angu-lar clustering analysis of Spitzer surveys (e.g., Oliver et al, 2004;de la Torre et al, 2007;Gilli et al, 2007;Magliocchetti et al, 2008), based mainly on mid-infrared (MIR) data, has been performed. Now, thanks to large space facilities, such as Herschel and Planck, results from longer wavelengths start to appear (e.g., Maddox et al, 2010;Cooray et al, 2010;Amblard et al, 2011;Magliocchetti et al, 2011;Planck Collaboration et al, 2011). With the data from the WISE satellite (Wright et al, 2010) we may soon hope for the all-sky measurement of MIR galaxies.…”
Section: Introductionmentioning
confidence: 99%